2014
DOI: 10.1117/12.2043332
|View full text |Cite
|
Sign up to set email alerts
|

Automated breast tissue density assessment using high order regional texture descriptors in mammography

Abstract: Breast cancer is the most common cancer and second leading cause of cancer death among women in the US. The relative survival rate is lower among women with a more advanced stage at diagnosis. Early detection through screening is vital. Mammography is the most widely used and only proven screening method for reliably and effectively detecting abnormal breast tissues. In particular, mammographic density is one of the strongest breast cancer risk factors, after age and gender, and can be used to assess the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Then, the pectoral muscle is detected by employing linear regression to fit all the identified pixels with the maximum gradient on a straight line/fit. Finally, all the pixels within the pectoral muscle are discarded from the segmented breast area as these pixels do not add useful/beneficial information for the classification task (Law et al , 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Then, the pectoral muscle is detected by employing linear regression to fit all the identified pixels with the maximum gradient on a straight line/fit. Finally, all the pixels within the pectoral muscle are discarded from the segmented breast area as these pixels do not add useful/beneficial information for the classification task (Law et al , 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies showed that extracting density features from the dense region 30 or retroareolar region 45 led to better prediction accuracy. In our study, the breast area was divided into five subregions according to intensity of each pixel, and all the density and texture features were computed within different subregions.…”
Section: Discussionmentioning
confidence: 99%
“…23,31,32 Once the breast region was identified, we performed a kclass fuzzy c means (FCM) clustering to partite it into several subregions and each one has relatively homogeneous density values. Instead of stratifying breast areas into dense and fatty regions only, 30,[33][34][35] more subregions were extracted and analyzed from the original breast depicted on mammogram. In this study, the number of clusters k was set to 5, so every breast region was separated into five areas.…”
Section: B Mammographic Subregions Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the most prevailing source of cancer-related deaths among women across the globe. Yearly, there are approximately 450, 000 deaths, out of which, breast cancer accounts for about 14% of all female cancer deaths ( [24]). Recent statistics says that 1 out of 10 women is affected by breast cancer in their lifetime.…”
Section: Introductionmentioning
confidence: 99%